Study guides

Q: What is 10 plus 10 X 0 plus 10?

Write your answer...

Submit

Related questions

It is: 110

x^2 + 13x + 30 = 0 x^2 + 10x + 3x + 30 = 0 x(x + 10) + 3(x + 10) = 0 (x + 3)(x + 10) = 0 x = -3 or x = -10

10

337,060 = (3 x 10^6) + (3 x 10^5) + (7 x 10^4) + (0 x 10^3) + (0 x 10^2) + (6 x 10^1) + (0 x 10^0)

If x is designated as "multiply," my answer is 0. If x is a "variable," my answer is 1.

20 as 10 x 0 = 0 so is just 10 + 10 = 20

0

X 2 + 8x -20 =0(x + 10)(x - 2)= 0x + 10 = 0 ............ x = -10andx - 2 = 0 ................. x = 2x = -10 or 2

x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10

1 x 8 plus 0 x 4 plus 0 x 2 plus 1 x 1. Total 9

0

(5+5) + (5-5) + (5 + 5 - 5) + (5 x 0) = 10 + 0 + 5 + 0 = 15

x2 +7x = 30 x2 +7x - 30 = 0 (x + 10)(x - 3) = 0 Now: x + 10 = 0 or x - 3 = 0 So: x = -10 or x = 3

x^2 + 14x + 40 factorises as (x + 10)(x + 4) so the roots are x = -10, -4.

If: (2x+10)(3x-15) = 0 => x^2-25 = 0 => (x-5)(x+5) = 0 So: x = 5 or x = -5

If: x^2+y^2+4x+6y -40 = 0 and x -y = 10 Then by rearranging: x = 10+y and 2y^2+30y+100 = 0 Solving the above quadratic equation: y = -10 and y = -5 Points of intersection by substitution are: (0, -10) and (5, -5)

The y-intercept happens when x = 0. In this case, that would be at the point (0, 10).

Rearrange the second equation as x = 10+y and then substitute it into the first equation which will create a quadratic equation in the form of: 2y2+30y+100 = 0 and when solved y = -10 or y = -5 Therefore the solutions are: x = 0, y = -10 and x = 5, y = -5

(1 x 10^6) + (0 x 10^5) + (0 x 10^4) + (0 x 10^3) + (0 x 10^2) + (0 x 10^1) + (0 x 10^0)

25,000,000 = (2 x 10^9) + (5 x 10^8) + (0 x 10^7) + (0 x 10^6) + (0 x 10^5) + (0 x 10^4) + (0 x 10^3) + (0 x 10^2) + (0 x 10^1) + (0 x 10^0)

(2 x 10^9) + (6 x 10^8) + (0 x 10^7) + (0 x 10^6) + (0 x 10^5) + (0 x 10^4) + (0 x 10^3) + (0 x 10^2) + (0 x 10^1) + (0 x 10^0)

110,000,000 = (1 x 10^10) + (1 x 10^9) + (0 x 10^8) + (0 x 10^7) + (0 x 10^6) + (0 x 10^5) + (0 x 10^4) + (0 x 10^3) + (0 x 10^2) + (0 x 10^1) + (0 x 10^0)

3x2 + 27x = 30 ∴ x2 + 9x - 10 = 0 ∴ (x + 10)(x - 1) = 0 ∴ x ∈ {-10, 1}

x2 + 20x + 4 = 0 x2 + 20x + 100 = 96 (x + 10)2 = 96 x + 10 = ±961/2 x = -10 ±961/2 x = -10 ±4√6

2x2+18x = 20 2x2+18x-20 = 0 x2+9x-10 = 0 (x+10)(x-1) = 0 x = -10 or x = 1